MECP2 mutations affect ciliogenesis: a novel perspective for Rett syndrome and related disorders - Angelisa Frasca; Eleonora Spiombi; Michela Palmieri; Elena Albizzati; Maria Maddalena Valente; Anna Bergo; Barbara Leva; Charlotte Kilstrup‐Nielsen; Federico Bianchi; Valerio Di Carlo; Ferdinando Di Cunto; Nicoletta Landsberger (EMBO Molecular Medicine)
Abstract Mutations in MECP2 cause several neurological disorders of which Rett syndrome (RTT) represents the best‐defined condition. Although mainly working as a transcriptional repressor, MeCP2 is a multifunctional protein revealing several activities, the involvement of which in RTT remains obscure. Besides being mainly localized in the nucleus, MeCP2 associates with the centrosome, an organelle from which primary cilia originate. Primary cilia function as “sensory antennae” protruding from most cells, and a link between primary cilia and mental illness has recently been reported. We herein demonstrate that MeCP2 deficiency affects ciliogenesis in cultured cells, including neurons and RTT fibroblasts, and in the mouse brain. Consequently, the cilium‐related Sonic Hedgehog pathway, which is essential for brain development and functioning, is impaired. Microtubule instability participates in these phenotypes that can be rescued by HDAC6 inhibition together with the recovery of RTT‐related neuronal defects. Our data indicate defects of primary cilium as a novel pathogenic mechanism that by contributing to the clinical features of RTT might impact on proper cerebellum/brain development and functioning, thus providing a novel therapeutic target.